Spectroscopic and energetic study and theoretical evaluation of flavone complexes with chromium(III) and iron(III) metals (Journal of the College of Basic Education, 2022)
New complexes of chromium (III) and iron (III) compounds with ligand flavone were prepared and identified by different spectroscopy methods and microelement analysis. The prepared complexes were identified by spectral methods (ultraviolet - visible and infrared rays), as well as determining the shape of the prepared complexes through magnetic measurements and electrical conductivity in DMSO dimethyl sulfoxide solution. From these studies and measurements, which indicate that the shape of the prepared complexes is octahedral.Theoretical processing of the complexes prepared in the gas phase was studied. This was done using the Hyper Chem.-6 program and the Chem.-Office program for molecular mechanics and semi-experimental calculations.The effectiveness of the prepared compounds was tested